(untitled) (Web of Teachers: Inderscience Research, 2024)
In this article, the financial literacy of the population is increased based on the continuity of financial education based on the original idea of the new educational model. Everyone can achieve financial stability and human well-being through financial literacy. It has been proven that everyone can build their future based on their financial capabilities if they have financial literacy, if they make conscious decisions in financial matters, if they avoid debt and financial problems. The scientific feature of the article is that it reflects the need to master the basic principles and skills of developing financial literacy, as well as to pay attention to education in this area. The current program of educating young people through the integration of sciences is to include financial literacy in textbooks.